To find (f+g)(1), we can start by rewriting it as:
![(f+g)(1)=f(1)+g(1)](https://img.qammunity.org/2023/formulas/mathematics/college/djokpepwp3fx9mnlhij3sgfoh2om8vib1n.png)
The function f and g have a set of pairs. We are looking for the pairs that have the first number "1", we want the second number. In both, they are the last pair.
For f this is (1,-2), so:
![f(1)=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/1avhlqxs1us4ixbj89hvvzax9e3svgny45.png)
For g this is (1,1), so:
![g(1)=1](https://img.qammunity.org/2023/formulas/mathematics/college/ozmiic49h00v9zylg2mwif0mdj611f7r7o.png)
So, substituting into the first expression, we have:
![(f+g)(1)=f(1)+g(1)=-2+1=-1](https://img.qammunity.org/2023/formulas/mathematics/college/81lojhybcwil922uq10l0iczsp5f29bxlx.png)